Agricultural pastures challenge the attractiveness of natural saltmarsh for a migratory goose. Issue 6 (24th May 2018) - Dokter, Adriaan M.; Fokkema, Wimke; Ebbinge, Barwolt S.; Olff, Han; van der Jeugd, Henk P.; Nolet, Bart A.
Abstract: Broad‐scale land conversions and fertilizer use have dramatically altered the available staging area for herbivorous long‐distance migrants. Instead of natural land, these birds rely increasingly on pastures for migratory fuelling and stopover, often conflicting with farming practices. To predict and manage birds' future habitat use, the relative advantages and disadvantages of natural (e.g. saltmarsh, intertidal) versus anthropogenic staging sites for foraging need to be understood. We compared the migratory staging of brent geese on saltmarsh and pasture sites in spring. Food quality (nitrogen and fibre content), antagonistic behaviour, and body weight were quantified at nearby sites in simultaneous seasons. Individuals were tracked with high‐resolution GPS and accelerometers to compare timing of migration and time budgets during fuelling. On pastures, birds rested more and experienced higher ingestion rates, similar or superior food quality and reduced antagonistic interactions than on saltmarsh. Brent geese using fertilized grasslands advanced their fuelling and migration schedules compared to those using saltmarsh. Pasture birds reached heavy weights earlier, departed sooner, and arrived in the Arctic earlier. Intertidal mudflats were frequently visited by saltmarsh birds during the day, and available food there (algae, some seagrass) was of higher quality than terrestrial resources. Availability of intertidal resources was an important factor balancing the otherwise more favourable conditions on pastures relative to saltmarsh. Synthesis and applications . Disadvantages of longer foraging effort, more antagonistic interactions and delayed fuelling schedules on traditional saltmarshes may cause geese to exchange this traditional niche in favour of pastures, especially in a warming climate that requires advancement of migratory schedules. However, due to its high quality, intertidal forage can complement terrestrial foraging, potentially removing the incentive for habitat switches to pastures. The relatively high quality of green algae and seagrass, and birds' remarkable preference for these resources when available, provides a key for managers to create landscapes that can sustain this specialist's intertidal lifestyle. To keep natural habitats attractive to staging geese with the purpose of preventing conflicts with farming practices, management actions should focus on conservation and restoration of saltmarsh and especially intertidal habitat. Abstract : Disadvantages of longer foraging effort, more antagonistic interactions and delayed fuelling schedules on traditional saltmarshes may cause geese to exchange this traditional niche in favour of pastures, especially in a warming climate that requires advancement of migratory schedules. However, due to its high quality, intertidal forage can complement terrestrial foraging, potentially removing the incentive for habitat switches to pastures. The relatively high quality of green algae and seagrass, and birds' remarkable preference for these resources when available, provides a key for managers to create landscapes that can sustain this specialist's intertidal lifestyle. To keep natural habitats attractive to staging geese with the purpose of preventing conflicts with farming practices, management actions should focus on conservation and restoration of saltmarsh and especially intertidal habitat.